The Effectiveness of Written ‘Peer Review’ Towards English 3 Students’ Writing Skill - Ma’rifatul Fadhilah (Vision: Journal for Language and Foreign Language Learning, 2017)
The writer conducted this research because the students of the non-English department, FITK UIN Semarang could not write text well. They still wrote text with random way, and they did not understand the social function, the generic structure and the language feature of the text. Using peer review in writing class, the writer intended to improve students' writing especially recount, descriptive, procedure, and cause and effect texts. The had two problems: 1). How is the implementation of ‘peer review' writing for the FITK students of 2014/2015?; 2). How is the writing improvement of FITK students of 2014/2015 after applying ‘peer review’ writing? There are some texts introduced to the FITK students. The students are expected to be able to write text. Through classroom action research implementing peer review, the students’ writing ability had been improved well.